Organic Production Practices and Technical Inefficiency of Durian Farms in Thailand - Wirat Krasachat (My University, 2012)
The primary purpose of this study is to measure and investigate organic production practices affecting technical inefficiency of durian farms in Thailand. This study applies a stochastic frontier production function approach to measure farm-specific technical inefficiency using the 2011 farm-level cross-sectional survey data of Thai durian farms in a single estimation technique applying the maximum likelihood estimation method. The non-negative technical inefficiency effects are modelled as a function of farm-specific socio-economic, organic production practice and other production management factors. The empirical results suggest two important findings. First, there is confirmation that producer's education, the application of organic farm system and soil improvement practices influenced the technical inefficiency of durian farms. Second, the considerable variability of fertiliser types does not have different impacts on technical inefficiency in Thai durian production in different farms. The results indicate advantages in increasing years of schooling and using organic farm practices in Thai durian farms. Therefore, the policies on encouraging farmers to increase continuing education and suggesting the farmers to use organic production practices in Thai durian farms are recommended to increase technical efficiency in durian production in Thailand.
Keywords: Productionpossibility frontier; Efficiency Analysis Using DEA